Sosialisasi Budidaya Tanaman Cabe (Capsicum Annuum L.) Di Desa Fadoro Lauru, Kecamatan Hiliduho, Kabupaten Nias - Suasti Damai Gulo; Dian Agung Sanora Laia; Restu Jaya Zendrato; Arman Rius Zendrato; David Trisman Zega (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
Fadoro Lauru Village, Hiliduho District, Nias Regency, has significant agricultural potential, but it has not been optimally utilized for the development of high-value horticultural commodities such as chili peppers (Capsicum annuum L.). A chili cultivation outreach activity conducted by student interns from the Agrotechnology Study Program at Nias University aimed to improve the community's technical knowledge, motivate productive land management, and encourage the adoption of sustainable agricultural innovations. The implementation method consisted of three stages: (1) interactive presentation of chili cultivation materials, (2) participatory discussions to explore farmers' experiences and challenges, and (3) distribution of chili seeds as a direct implementation step. The results of the activity demonstrated high community enthusiasm, increased technical understanding, and readiness to implement chili cultivation practices independently. This activity also strengthened the synergy between students, the village government, and the community as a foundation for sustainable local agricultural development.